Synthesis and In Vitro Evaluation of E- and Z-Geometrical Isomers of PSS232 as Potential Metabotropic Glutamate Receptors Subtype 5 (mGlu5) Binders - Milicevic Sephton, Selena; Mu, Linjing; Dragic, Martina; Krämer, Stefanie D.; Schibli, Roger; Ametamey, Simon M. (Synthesis, 2013)
Based on the core structure of [11C]-ABP688, our group developed a novel fluorine-18 labeled PET radiotracer, (E)-[18F]-PSS232, with significantly improved in vivo properties compared to the earlier fluorine-18 derivative [18F]-FDEGPECO. The synthetic approach used to obtain PSS232 and the radiolabeling precursor mesylate is disclosed as well as the evaluation of the two geometrical isomers of PSS232. In vitro displacement assays showed higher binding affinity of the E-geometrical isomer (1 nM vs 15 nM, for Z-isomer), which was, for this reason, selected for radiolabeling. One-step radiolabeling conditions (K222/18F–, DMSO, 95 °C, 10 min) to synthesize (E)-[18F]-PSS232 from the mesylate via nucleophilic substitution are described. At ambient temperature, (E)-[18F]-PSS232, with log D7.4 value of 2.0, was chemically stable over six hours in the presence of sodium ascorbate as a radical scavenger.
Keywords: mGlu5; PET imaging; PSS223; PSS232; ABP688